(untitled) (Grande Medical Journal, 2024)
The emergence of artificial intelligence (AI) has opened up a new realm of possibilities across various industries, with healthcare being no exception. AI has shown immense potential to revolutionize medical practices, from early disease detection and personalized treatment plans to accelerating drug discovery. However, these advancements also bring substantial challenges and implications that require careful consideration to ensure AI integration serves the best interests of both patients and healthcare providers.